A RHOMBIC PATCH MONOPOLE ANTENNA WITH MODIFIED MINKOWSKI FRACTAL GEOMETRY FOR UMTS, WLAN, AND MOBILE WIMAX APPLICATION - Chatree Mahatthanajatuphat; Somchai Saleekaw; Prayoot Akkaraekthalin; Monai Krairiksh (My University, 2009)
This paper presents a rhombic patch monopole antenna applied with a technique of fractal geometry.The antenna has multiband operation in which the generator model, which is an initial model to create a fractal rhombic patch monopole, is inserted at each center side of a rhombic patch monopole antenna.Especially, a modified ground plane has been employed to improve input impedance bandwidth and high frequency radiation performance.The proposed antenna is designed and implemented to effectively support personal communication system (PCS 1.85-1.99GHz), universal mobile telecommunication system (UMTS 1.92-2.17GHz), wireless local area network (WLAN), which usually operate in the 2.4 GHz (2.4-2.484GHz) and 5.2/5.8bands, mobile worldwide interoperability for microwave access (Mobile WiMAX), and WiMAX, which operate in the 2.3/2.5 GHz (2.305-2.360GHz/2.5-2.69GHz) and 5.5 GHz (5.25-5.85GHz) bands.The radiation patterns of the proposed antennas are similar to an omnidirectional radiation pattern.The properties of the antenna such as return losses, radiation patterns and gain are determined via numerical simulation and measurement.
Keywords: WiMAX; UMTS frequency bands; Fractal antenna; Antenna Design and Analysis